Factors of constructive process optimization in velocity-layer devices - Nadezda A Gil; Victor P. Zharov; Evgeny A. Smekhunov (Advanced Engineering Research)
The work objective is to study the fundamental parametric solutions to create the equipment for the oxygen enrichment of water in the closed water systems in recycling. It is assumed to achieve the effect of disinfection excluding the addition of oxygen into water from special containers. For a variety of advantages, velocity-layer devices (VLD) are chosen as a target of research. In the known development of these devices there are some questions on the fundamental solutions; besides, the effectiveness of factors for the oxygen enrichment of water is not determined. The logical analysis of the existing data on the processes taking place in the VLD, analytical methods of problem-solution, screening studies on the impact of some factors by applying a known control equipment, and statistical data processing, are used as research techniques. As a result of the work performed, the most significant factors operating in the velocity-layer devices are identified. The searching and screening experiments have shown that the cavitation and occurrence of free air in the treatment chamber have the greatest impact on the oxygen enrichment of water and the water disinfection for aquaculture. Besides, to reduce energy losses, the gaps between the magnetic conductors should be reduced as much as possible. The results of these experiments allow offering the design that provides the prevalence of the mentioned factors in the treatment of the wastewater for aquaculture.